IMPACTOS SOCIOCULTURALES GENERADOS POR LAS ACTIVIDADES TURÍSTICAS EN LA CIUDAD DE QUEVEDO - Bardi Zamora, Jokasta Juley (2022)
This research project is a document about the sociocultural impacts generated by tourist activities in the city of Quevedo, because tourism in the city is currently in constant growth and a written support of the benefits and possible actions is necessary. that should be considered to take advantage of this situation among citizens. To obtain information, techniques and tools were applied to obtain data and verified information, using surveys applied to a sample of the Quevedeña population, allowing direct knowledge of their perception of tourism in the city, as well as the formulation of interviews. to the head of tourism and to owners of localities destined to the conservation of the typical and traditional food of Quevedo. Tourism is a phenomenon that has been strengthened over the years with increasing intensity and emerging in a greater number of destinations around the world. It can be understood as a set of activities carried out by human beings while traveling and staying in places other than their usual environment, for leisure, work or other reasons. In addition, it is an economic activity that has an impact on society, not only because of its economic activity but also because of the large number of people who carry it out and because of its wide geographical distribution. It can be concluded that the sociocultural impacts generated by tourist activities in the city of Quevedo are positive with the generation of employment, infrastructure conservation and negative, such as the lack of security in tourist towns and the conservation of typical gastronomy, due to this arises the approach of proposals for the generation of employment through the expansion of services in existing tourist resources such as the river.